Structural, optical and electrical properties of ZnO/ZnAl2O4 nanocomposites prepared via thermal reduction approach - Salih, Ethar Yahya; Mohd Sabri, Mohd Faizul; Hussein, Mohd Zobir; Sulaiman, Khaulah; Mohd Said, Suhana; Saifullah, Bullo; Ali Bashir, Mohamed Bashir (Springer, 2018)
ZnO/ZnAl2O4 nanocomposites (Z r A-MMO) with homogeneously distributed ZnAl2O4 nanoparticles in the interpenetrating network of ZnO were successfully prepared via two-step solution process, namely co-precipitation of Zn/Al–NO3 layered double hydroxide (Z r A-LDH) precursor and thermal treatment methods. The effect of cation molar ratio (r) between Zn2+ and Al3+ on the morphological, structural, thermal, optical as well as electrical properties of ZnO-based MMOs was investigated in detail. A mechanism study related to the surface modification, optical band edge alteration as well as improvement of electrical conductivity after phase transformation from LDH to MMO was also elucidated. The optimum Z5A-MMO sample presents the highest electrical conductivity of 8.23 × 10−3 S/cm as compared to 7.26 × 10−7 S/cm for the standard ZnO nanocrystal. It is believed that the bathochromic shift in optical band gap of Z5A-MMO plays a pivotal role in facilitating the photoemission process and leads to the increase in number of carrier concentration in the sample. This method could provide alternative pathways for fabricating a high electrical conductivity MMO-based material and benefit in future optoelectronic devices.